2021
DOI: 10.11591/ijeecs.v23.i1.pp293-301
|View full text |Cite
|
Sign up to set email alerts
|

A survey on advanced transmission technologies for high bandwidth and good signal quality for high-speed railways

Abstract: Ahigh-speedrailway (HSR) has gained very high popularity for passengersdue to the fast, reliable, economical and convenient during traveling a verylong-distance journey. Thedemandfor advancedbroadbandservices such aswatching4K movies, cloud computing andonline gaming, has exponentiallyincreased fortravelerson thehigh-speedtrain(HST).The HSTcan’t providegood bandwidth to facilitate these services for travelers via existingtechnologies such as cellular networksand satellite networks because offrequent handoffs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…where the vector 𝒔 is a column vector representing the data symbols after pilot-symbols insertion and serialto-parallel conversion, 𝒔 𝑑 = [𝑠 𝒅 (1), 𝑠 𝒅 ( 2…”
Section: Proposed System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where the vector 𝒔 is a column vector representing the data symbols after pilot-symbols insertion and serialto-parallel conversion, 𝒔 𝑑 = [𝑠 𝒅 (1), 𝑠 𝒅 ( 2…”
Section: Proposed System Modelmentioning
confidence: 99%
“…Orthogonal frequency division multiplexing (OFDM) is a multi-carrier modulation technique widely implemented in broadband wireless communication systems such as long-term evolution (LTE) and all of the most recent Wi-Fi standards due to its high spectral efficiency and robustness when operating in frequency selective fading environments [1]. On the other hand, erroneous channel estimation is a crucial issue for wireless communication systems operating in frequency-selective fading channels, since channel-estimation errors might lead to considerable performance loss [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that it can get wide-band facility by using different channels of the OTDM system. The second one, which is used the orthogonal frequency division multiplexing (OFDM), MIMO, and radio over-fiber (ROF) as reported in [14]. This work focused on improving the signal transmitted quality using three above technologies.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to other algorithms, the findings of the algorithms primary domain controller (PDC) and direct cable connection (DCC) show a greater success rate and cost effectiveness. A resource provisioning technique was presented to help hybrid cloud infrastructures meet the deadline demands of dataintensive applications [30]. The task scheduling literature review is presented in Table 1.…”
mentioning
confidence: 99%